1993
DOI: 10.1159/000282516
|View full text |Cite
|
Sign up to set email alerts
|

Use of Maintenance Intravesical Bacillus Calmette-Guérin (BCG), with or without Intradermal BCG, in Patients with Recurrent Superficial Bladder Cancer

Abstract: To study maintenance Bacillus Calmette-Guérin (BCG) therapy we treated 49 patients with recurrent superficial bladder cancer pTa and/or carcinoma in situ, failing previous intravesical chemotherapy. They received 20 intravesical instillations in 1 year, with or without 6 intradermal inoculations. Side effects were frequent, causing treatment stop in 14 patients (29%). Drug-induced cystitis was the most frequent side effect, seen in 29 patients (59%). Forty-two patients were evaluable for response. During the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…These trials (1) covered previously tested indications for which clear results had not been obtained; (2) investigated variations in dose, 104 - 107 administration route 108 - 111 and schedule; 111 - 113 and (3) evaluated the safety and efficacy of BCG or BCG components in a few previously untested or scarcely tested settings, including lymphoma, 114 and ovarian cancer 115 - 117 . These clinical studies led to a remarkable refinement in the dosage and schedule of BCG immunotherapy, thus lowering both the incidence and severity of BCG-associated side effects (mainly consisting of fever, hematuria, bladder irritation/infection and a potentially lethal, but very rare, systemic reaction) 118 .…”
Section: Bacillus Calmette-guérinmentioning
confidence: 99%
“…These trials (1) covered previously tested indications for which clear results had not been obtained; (2) investigated variations in dose, 104 - 107 administration route 108 - 111 and schedule; 111 - 113 and (3) evaluated the safety and efficacy of BCG or BCG components in a few previously untested or scarcely tested settings, including lymphoma, 114 and ovarian cancer 115 - 117 . These clinical studies led to a remarkable refinement in the dosage and schedule of BCG immunotherapy, thus lowering both the incidence and severity of BCG-associated side effects (mainly consisting of fever, hematuria, bladder irritation/infection and a potentially lethal, but very rare, systemic reaction) 118 .…”
Section: Bacillus Calmette-guérinmentioning
confidence: 99%
“…Several studies and meta-analysis data indicate that the use of thiotepa, MMC, doxorubicin and epirubicin do not significantly change the progression and tumorspecific survival rates [6,[32][33][34]49,100,101]. In contrast, evidence from controlled, randomized trials suggests a significant reduction in tumor progression and tumor-specific mortality rates with BCG administration [6,13,23,52,92,102,103]. The reasons for the apparent advantage of intravesical BCG over chemotherapy in the intermediate-and long-term prevention of tumor recurrence and progression of high-stage and grade disease is unclear.…”
Section: Intravesical Chemoprophylaxis or Bcg Immunoprophylaxismentioning
confidence: 99%
“…It has been demonstrated that the use of BCG was associated with a relative risk for UBC recurrence of 0.39 [29,30]. These encouraging results were sustained even in patients with recurrent or aggressive disease, including patients whose prior intravesical chemotherapy had failed [16,31]. …”
Section: Intravesical Bacillus Calmette–guerin Immunotherapymentioning
confidence: 99%